Productividad en Función de la Capacitación Ofertada por el Servicio de Integración Laboral del FENEDIF - Villacrés Varas, Vladimir Jahir (2017)
This case study aims to take into account a population whose needs usually go unnoticed in today's society, in a world that is more accelerated, laborious, conflictive and competitive at the same time, people with disabilities, whether physical or become easily identified as vulnerabilities worldwide. Even more so when it comes to a country like ours with an unstable economy, where every person struggles day by day to provide the necessary resources to support their home and often fail to do so, opportunities for people with disabilities are less and less encouraging and generally they are the ones who make up a large part of the unemployment rate in the country